Consensus guidelines for the treatment of Nephrotic Syndrome in Children of Pakistan: Endorsed by Pakistan Pediatric Association- Nephrology Group - Lanewala, Ali Asghar A; Hashmi, Seema; Tresa, veena; Khatri, Sabeeta; Bajeer, Irshad Ali; Ehsan, Afshan; Moorani, Khemchand N; Asim, Sadaf; Abro, Bilquis (Pakistan Journal of Kidney Diseases, 2021)
This guideline was prepared for the pediatric nephrologists and the genral pediatrician to review the subject and update with the treatment of different manifestaion of childhood nephrotic syndrome.